Analisis Permintaan Uang Riil di Indonesia - Halia Butra Aini; Syamsurijal Tan; Arman Delis (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2016)
Abstract. This research aims to determine how the relationship between variables GDP, inflation rate, interest rate and exchange rate against the real demand for money in Indonesia. The data used in the empirical study of a sequence of data monthly time of year 2011.01 through 2015. 12 from Central Bank of Indonesia and the Central Statistics Agency (BPS). The analysis method in this research is Vector Error Correction Model (VECM). The results showed that there is a one-way relationship between the real demand for money on interest rates, one-way relationship between GDP against exchange rate and interest rates, then the one-way relationship between inflation against exchange rate. Then, there is a two-way relationship between GDP and the real demand for money, two-way relationship between inflation and demand for real money, two-way relationship between GDP and inflation, two-way relationship between interest rates and inflation as well as two-way relationship between interest rates and exchange rate. The results also showed GDP does not significantly affect the real demand for money. Variable exchange rate positively and significantly affect the real demand for money in the short term. While the interest rate a significant negative effect on the real demand for money. The real demand for money in Indonesia in the long term positively and significantly influenced by variables GDP. While the variable exchange rate and interest rate negative effect. Keywords: Real demand for money, Inflation, GDP, Exchange rate, Interest rate, Abstrak. Penelitian ini bertujuan untuk mengetahui seberapa keterkaitan antar variabel pdb, tingkat inflasi, tingkat suku bunga dan nilai tukar terhadap permintan uang riil di Indonesia. Data yang digunakan dalam kajian empiris ini merupakan data runtutaan waktu bulanan dari tahun 2011.01 sampai 2015. 12 yang berasal dari Bank Indonesia dan Badan Pusat Statistik (BPS). Alat analisis yang digunakan yaitu Vector Error Correction Model (VECM). Hasil penelitian menunjukkan terdapat hubungan searah antara permintaan uang riil terhadap tingkat suku bunga, antara PDB terhadap Kurs dan tingkat suku bunga, antara Inflasi terhadap Kurs. Terakhir, terdapat hubungan dua arah antara PDB dan permintaan uang riil, hubungan dua arah antara Inflasi dan permintaan uang riil, hubungan dua arah antara PDB dan Inflasi, hubungan dua arah antara tingkat suku bunga dan Inflasi serta hubungan dua arah antara tingkat suku bunga dan Kurs. Hasil penelitian ini juga menunjukan PDB tidak signifikan mempengaruhi permintaan uang. Variabel Kurs berpengaruh positif dan signifikan mempengaruhi permintaan uang riil dalam jangka pendek. Sedangkan tingkat suku bunga berpengaruh negatif dan signifikan terhadap permintaan uang riil. Permintaan uang riil di Indonesia dalam jangka panjang dipengaruhi secara positif dan signifikan oleh variabel PDB. Sedangkan variabel Kurs dan suku bunga berpengaruh negatif.Kata Kunci: Permintaan Uang Riil, Inflasi, PDB, Kurs, Suku Bunga